A Nonuniform Sampling Lifetime Estimation Technique for Luminescent Oxygen Measurements for Biomedical Applications - Costanzo, Ian; Sen, Devdip; McNeill, John; Guler, Ulkuhan (IEEE journal of solid-state circuits, 2025)
This article presents a novel technique that is immune to offset, enabling precise determination of the lifetime of luminescent materials. The technique is specifically applied to measure transcutaneous oxygen, an indicator of oxygen that diffuses through the skin and reflects arterial oxygen levels. Unlike intensity-based measurements, lifetime-based luminescence measurements are superior because they decouple oxygen information from confounding factors. The technique presented in this work involves measuring the time difference between fixed-voltage steps to extract the time constant of a decaying exponential, which represents the lifetime of luminescence. We propose a novel switched-capacitor circuit that enables long integration times and prevents the front-end amplifier from saturating. The analog subsystem was realized in 180-nm CMOS technology via a transimpedance amplifier (TIA) with a gain bandwidth product of 10 MHz, a comparator, and a switched capacitor circuit. The measured mean error is as accurate as 1.9% without postprocessing. During a 130~{μ } s measurement period, the readout circuit consumes a maximum of 16~{μ } J per calculation with a {\text {FoM}_{W}}{=}177 nJ/conv. Preliminary human subject tests have demonstrated that the sensor can effectively detect changes in transcutaneous oxygen levels resulting from arterial occlusion.